Estratégia de amostragem de riscos químicos: proposta de um modelo para uma instalação de distribuição de combustíveis líquidos - Chaves, Claudia Aguas (2003)
With the growing globalization and development of new work processes, worker heath and safety protection and prevention are graduaily transforming into strategic issues, in the sense that they can significantiy impact the abiiity of businesses to achieve their objectives. Considering, then, the scarcity of availabie resources, businesses must prioritize and adjust their invesfments in these areas. The better the existing heaith and safety hazards in the workplace are understood, the better priorities are determined to reduce or eiiminate these hazards. In addition, the greater the confidence and representativeness of the resuits obtained from worker exposure evaluations, the greater the guarantee that the investments are directed to those areas of highest risk. In this manner, the science of Occupational Hygiene, through the appiication of ali of it s phases, specificaliy the phase of assessment or sampling of environmentai hazards, plays the fundamental role of providing detailed knowledge of these exposures. The objective of this work was to review the decisionmaking process of developing a strategy for sampling and assessing chemical hazards and to appiy this process in a petroleum fuels distribution faciIity. in the end, this study is intended to present a contribution to the professionais that design (or promote the design of) Occupational Safety, Health and Hygiene management programs and systems, to expand the knowiedge base such that they can adopt proactive measures, measures that prevent the occurrence of workplace illness and accidents.